2006
DOI: 10.1111/j.1540-8175.2006.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary Syndrome and Right Ventricular Diastolic Functions: An Echocardiographic Examination

Abstract: Right ventricular diastolic dysfunction rate is high in chronic liver diseases. In the presence of HPS, right ventricular diastolic dysfunction is more remarkable in patients than those without HPS. Right ventricular diastolic dysfunction may result in dilatation and hypertrophy in the right heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
4
32
1
Order By: Relevance
“…A previous post-mortem analysis revealed a high rate of RV chamber dilatation in approximately one-third of patients with cirrhosis [21]. Similar to the findings of the present study, others have demonstrated that patients with cirrhosis have a larger RV dimension than controls when measured by echocardiography [16,22,23]. In the present study, the RV dimension is significantly increased in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
“…A previous post-mortem analysis revealed a high rate of RV chamber dilatation in approximately one-third of patients with cirrhosis [21]. Similar to the findings of the present study, others have demonstrated that patients with cirrhosis have a larger RV dimension than controls when measured by echocardiography [16,22,23]. In the present study, the RV dimension is significantly increased in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
“…Radiographic pulmonary interstitial changes and echocardiographic changes were more frequently seen in patients with HPS than in controls, as has been shown in previous studies. [18][19][20][21] The most important finding in this study is that HPS was associated with a significantly increased risk of death. This result persisted even after accounting for age, sex, MELD score, liver transplantation, and other potential confounders.…”
Section: Discussionmentioning
confidence: 62%
“…20 Intriguingly, demographical data were not affiliated with the occurrence of right-ventricular hypertrophy in our patients, but alcoholic cirrhosis, NASH-cirrhosis, and cryptogenic cirrhosis were independent risk factors for this cardiac lesion. Again, patients with a NASH-cirrhosis were at the highest risk for right-ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 81%